Handwashing Dance Sebagai Literasi Kesehatan Anak Usia Dini pada Masa Pandemi Covid-19 - Besse Nirmala; Maitha Saraswati; Haerul Annuar (Jurnal Kreatif Online, 2021)
This study aimed to implement handwashing dance as children's health literacy during the Covid-19 pandemic. This research was conducted in group B2 TK Negeri Model Terpadu Madani with children aged 5-6 years as research subjects. This research used a qualitative approach. Data were collected through observation, interviews and documentation. The results showed that there were six children who were able to carry out the steps to wash their hands properly without assistance, and three children who were able to do the steps with the help of the teacher. In cognitive aspects, children were able to mention the right time to wash their hands, know the benefits of washing hands, and mention the correct order of washing hands. In affective aspects, children want to wash their hands using soap, not waste water when washing their hands, feel happy, want to queue, dry their hands using a cloth or tissue, and throw used tissues into the trash. Meanwhile, in psychomotor aspect children can take steps to wash their hands properly.